The Guideline for Ecotourism Development in Lay Kao Kob Cave, Trang - รัตนพันธุ์ กนกรัตน์; นิลออ นุชนาฎ; จิ้วตั้น บุญจงรักษ์; รัตนพันธุ์ วรพจน์ (JOURNAL OF SOUTHERN TECHNOLOGY, 2019)
This research aimed to study the potential of tourism resources, the road around and the guideline for ecotourism development in Lay Kao Kob Cave, Trang. The sample group from Taro Yamane were 286 people who have lived in moo 1, Kao Kob Village. They were selected by using the accidental sampling and the questionnaires as a research instrument. The questionnaires were assessed by examinations for quality then, they were tested by 20 sampling. To analyze statistical data, the measures namely; frequency, percentage, mean and standard deviation were used in this research. From the research found that the total potential of tourism resources was at a high level ( =4.08, S.D. = 0.89). When considering each aspect, this potential of plants were at a high level ( = 4.18, S.D. = 0.83), wild animals were at a high level ( = 3.98, S.D. = 0.95) and ecotourism was at a high level ( = 4.08, S.D. = 0.89). Moreover, the majority of the villagers (91.6 %) agree that there was an ecotourism development in Lay Kao Kob Cave. In addition, public participation in development were the 53.5 %, followed by the governor by 31.8 %, and the district chief by 4.7 % respectively. Furthermore, the guideline for ecotourism development were that the villagers agreed with natural trail by guide (97.6 %), themselves (94.8 %) and cycling (89.2 %); however, they disagreed by horse riding (78.0 %).